Immature mesenchymal stem cell-like pericytes as mediators of immunosuppression in human malignant glioma - Sahm, Katharina; Sahm, Felix; Opitz, Christiane; Lanz, Tobias; Oezen, Iris; Couraud, Pierre-Olivier; Deimling, Andreas von; Wick, Wolfgang; Platten, Michael (Journal of neuroimmunology, 2013)
Malignant gliomas are primary brain tumors characterized by profound local immunosuppression. While the remarkable plasticity of perivascular cells - resembling mesenchymal stem cells (MSC) - in malignant gliomas and their contribution to angiogenesis is increasingly recognized, their role as potential mediators of immunosuppression is unknown. Here we demonstrate that FACS-sorted malignant glioma-derived pericytes (HMGP) were characterized by the expression of CD90, CD248, and platelet-derived growth factor receptor-β (PDGFR-β). HMGP shared this expression profile with human brain vascular pericytes (HBVP) and human MSC (HMSC) but not human cerebral microvascular endothelial cells (HCMEC). CD90+PDGFR-β+perivascular cells distinct from CD31+ endothelial cells accumulated in human gliomas with increasing degree of malignancy and negatively correlated with the presence of blood vessel-associated leukocytes and CD8+ T cells. Cultured CD90+PDGFR-β+HBVP were equally capable of suppressing allogeneic or mitogen-activated T cell responses as human MSC. HMGP, HBVP and HMSC expressed prostaglandin E synthase (PGES), inducible nitric oxide synthase (iNOS), human leukocyte antigen-G (HLA-G), hepatocyte growth factor (HGF) and transforming growth factor-β (TGF-β). These factors but not indoleamine 2,3-dioxygenase-mediated conversion of tryptophan to kynurenine functionally contributed to immunosuppression of immature pericytes. Our data provide evidence that human cerebral CD90+ perivascular cells possess T cell inhibitory capability comparable to human MSC and suggest that these cells, besides their critical role in tumor vascularization, also promote local immunosuppression in malignant gliomas and possibly other brain diseases.
Gesehen am 29.11.2021